Presenting a conceptual model of leakage management system in urban water supply network from two preventive and operational perspectives (Case study of Tokyo and Tehran metropolises) - Saeed Mohammadi; Mahdi Najafzadeh; Mohammad Gheibi; Zahra Kian; Amir Takhtravan; Reza Aghlmand (Annals of Environmental Science and Toxicology - Peertechz Publications, 2021)
The existence of leakage in the urban water supply network can be considered one of the main challenges in the country's water industry. The purpose of this study is a comparative comparison of water leakage management patterns in Tokyo and Tehran. In this study, the existing documents in the field of water leakage management in both cities were collected, classified, and evaluated. A comparison at the level of preventive measures showed that the city of Tokyo has a conceptual model (with an effective water ratio of more than 98%) with «corrective» subdivisions including old network management and providing solutions for maintenance and repair of the current network and also subdivisions including «technology development» and «education.» However, in Tehran, due to financial constraints, the preventive approach (PM11) is entirely passive, and emergency maintenance (EM2) units usually enter into operation after the incident. Operational comparisons showed that the Tokyo Water Leakage Control System consists of two main parts: "continuous monitoring" and "measures commensurate with the type of challenge" and is based on strategic policies. In Tehran, the movement towards using new technologies to control leakage in urban water supply networks has been significant; However, these measures are not based on a plan and have created unbalanced growth in this regard.